2017
DOI: 10.1097/ta.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

Selective versus nonselective embolization versus no embolization in pelvic trauma

Abstract: Therapeutic, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 18 publications
0
32
0
8
Order By: Relevance
“…We suspect that it may be difficult to differentiate between bone marrow and arterioles as the source of contrast extravasation during CT examination soon after a pelvic fracture, and our results suggest that evidence of CE during CT may not be a suitable major indication for AE, despite this being previously recommended [7,21]. Dreizin et al [22] have suggested that the use of AE should be guided instead by the hematoma volume when arterial bleeding is detected during CT. We believe that angiography and AE should be performed more selectively, perhaps on the basis of non-response to resuscitation, a continuing decrease in hemoglobin concentration without evidence of bleeding from other sources, and the absence of arterial blush during CT. Non-selective embolization is considered a hemostatic procedure for hemodynamically unstable patients with pelvic fractures [7,23], although recent studies have focused on selective or super-selective embolization to decrease the negative effects of non-selective embolization in cases of vasospasm or rich collateral arterial networks within the pelvis [24,25]. Thus, we evaluated the outcomes of different AE strategies, given the fact that AE interventions might be accompanied by a high complication rate after these patients undergo osteosynthesis to treat their unstable pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that it may be difficult to differentiate between bone marrow and arterioles as the source of contrast extravasation during CT examination soon after a pelvic fracture, and our results suggest that evidence of CE during CT may not be a suitable major indication for AE, despite this being previously recommended [7,21]. Dreizin et al [22] have suggested that the use of AE should be guided instead by the hematoma volume when arterial bleeding is detected during CT. We believe that angiography and AE should be performed more selectively, perhaps on the basis of non-response to resuscitation, a continuing decrease in hemoglobin concentration without evidence of bleeding from other sources, and the absence of arterial blush during CT. Non-selective embolization is considered a hemostatic procedure for hemodynamically unstable patients with pelvic fractures [7,23], although recent studies have focused on selective or super-selective embolization to decrease the negative effects of non-selective embolization in cases of vasospasm or rich collateral arterial networks within the pelvis [24,25]. Thus, we evaluated the outcomes of different AE strategies, given the fact that AE interventions might be accompanied by a high complication rate after these patients undergo osteosynthesis to treat their unstable pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…Non-selective embolization is considered a hemostatic procedure for hemodynamically unstable patients with pelvic fractures [7,23], although recent studies have focused on selective or superselective embolization to decrease the negative effects of non-selective embolization in cases of vasospasm or rich collateral arterial networks within the pelvis [24,25]. Thus, we evaluated the outcomes of different AE strategies, given the fact that AE interventions might be accompanied by a high complication rate after these patients undergo osteosynthesis to treat their unstable pelvis.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-selective embolisation for haemodynamically unstable patients with pelvic fractures is considered a haemostatic procedure [7,22], in case of vasospasm or rich collateral arterial network within the pelvis, current studies have focused on selective or super-selective embolisation to decrease the negative impacts of non-selective embolization [23,24]. Since the AE intervention might be accompanied by a high complication rate after these patients undergo osteosynthesis to treat their unstable pelvis, we also assessed the outcomes of different AE approaches.…”
Section: Discussionmentioning
confidence: 99%